Applying augmented reality on the teaching and studying diesel high pressure pump - Nguyễn Tấn Ngọc (Journal of Technical Education Science, 2020)
Nowadays, Diesel engine is still a major part of the transportation around the world, especially in Vietnam. The high-pressure pump is one of the key factor resulting in the working performance of the engine. The high-pressure pump such as PF, PE or VE is applied in lots of transportation, such as car, ship, vessel in Vietnam. This paper is an introduction for applying the augmented reality in teaching and studying diesel engine in HCMC University of Technology and Education, focusing on the diesel high-pressure pump. Augmented reality (AR) is a new way of information sharing and interaction. AR in education brings truly unlimited possibilities for teaching and learning process. Additional reality provides the unique cognition path with immersive real-life simulations.